Orthotes and Diairesis of Names. The Question of Method in Prodicus - Brancacci, Aldo (Peitho. Examina Antiqua, 2017)
The question of the method was central in the thought and teaching of Prodicus. We have abundant information on this method but it is, probably, closely connected to various other issues (natural investigations, rhetoric and rhetorical theory, questions concerning the gods, ethics), on which we are less well informed. The right method to solve diverse linguistic problems comprised two moments and not just one as it frequently assumed. Similarly, the terms orthotes and diairesis of names, which appear in the sources, do not designate one single and simple procedure, but rather a double and more complex one, which is reconstructed in this article and whose objectives are clarified.